Work positive in a negative world: redefine your reality and achieve your business dreams - Faucette, Joey. (Irvine, CA : Entrepreneur Press, 2011)
"Step away from the negative shadows cast by the world's clouds and discover a positive reality -- wide open with new solutions and opportunities. Unleash your power to Work Positive as you perceive, conceive, believe, achieve, and receive remarkable results in your business." --Publisher.
Includes bibliographical references and indexes.
Keywords: Attitude (Psychology).; Success in business